Are they half as strong as they used to be? An experiment testing whether age-related social comparisons impair older people's hand grip strength and persistence. Issue 3 (22nd May 2012) - Swift, Hannah J; Lamont, Ruth A; Abrams, Dominic
Abstract : Objective: To assess how age-related social comparisons, which are likely to arise inadvertently or deliberately during assessments, may affect older people's performance on tests that are used to assess their needs and capability. Design: The study randomly assigned participants to a comparison with younger people or a no comparison condition and assessed hand grip strength and persistence. Gender, education, type of residence, arthritis and age were also recorded. Setting: Age UK centres and senior's lunches in the South of England. Participants: An opportunity sample of 56 adults, with a mean age of 82.25 years. Main outcomes measures: Hand grip strength measured using a manual hand dynamometer and persistence of grip measured using a stopwatch. Results: Comparison caused significantly worse performance measured by both strength (comparison =6.85 kg, 95% CI 4.19 kg to 9.5 kg, control group =11.07 kg, 95% CI 8.47 kg to 13.68 kg, OR =0.51, p=0.027) and persistence (comparison =8.36 s, 95% CI 5.44 s to 11.29 s; control group =12.57 s, 95% CI 9.7 s to 15.45 s, OR =0.49, p=0.045). These effects remained significant after accounting for differences in arthritis, gender, education and adjusting for population age norms. Conclusions: Due to the potential for age comparisons and negative stereotype activation during assessment of older people, such assessments may underestimate physical capability by up to 50%. Because age comparisons are endemic, this means that assessment tests may sometimes seriously underestimate older people's capacity and prognosis, which has implications for the way healthcare professionals treat them in terms of autonomy and dependency.